Document Security System Using Arduino-Based Fingerprint And Rfid Module - Mohamad Irkam; Toni Wijanarko Adi Putra (University of Science and Computer Technology, 2023)
Documents are valuable/important letters that can be used as evidence of printed or written information. The company where the author conducted research is a company operating in the logistics sector, which of course has a special document storage room, namely the Accounting room . The use of plastic folders containing documents and safes as a place to store important documents and files still carries a lot of risk of misuse and loss. The title of this research is Document Security System Using Arduino- Based Fingerprint and RFID Modules . One of the aims of this research is to minimize loss and prevent misuse of documents/files placed in plastic folders. A security system using fingerprint and RFID is very good to apply as document security because it has double security. The system created uses a fingerprint as a signal breaker or RFID tag electromagnetic waves which are attached to a folder containing important documents/files belonging to the company. This system is also supported by an Arduino kit Uno with an Atmega328 microcontroller as the brain for processing data from the fingerprint sensor and RFID Reader functions as an electromagnetic wave identification system for RFID Tags , therefore two pieces of hardware are needed, called Tags and Readers . Apart from the three main components mentioned, there are several other components used in making this document security system, namely micro SD kit, buzzer, push button, servo . Creating this system is very important to limit misuse of documents and the risk of losing documents in a company.